产权的确立是消除中国矿业开采中外部性的有效对策 = Legal remedies for externalities : establishment of property rights in China's mining and quarrying industry - 李明凯 Li, Ming Kai (2008)
This paper recounts the evolution of China's legislation governing mining and quarrying over the past two decades. It describes how property rights have been established following a series of law reforms that gradually liberlize and marketize the mining rights.